Dysphagia: Indian perspective an often overlooked clinical experience (Bangladesh Journal of Otorhinolaryngology, 2012)
Purpose: To find-out causes of dysphagia in an Indian population and to assess whether the cases termed globus actually has some underlying cause.Methods: History elucidation, ENT examination, neurological check up and neuromuscular examination. Barium swallows of esophagus, upper flexible GED scopy, flexible laryngoscopy, X-ray cervical spine. X-ray soft tissue neck lateral view, CXR, CT scan, MRI and diagnostic rigid esophagoscopy.Results: Hypopharyngeal carcinoma (pyriform fossa) 25% (30) and esophagitis, stricture, caustic injury, webs, 25% (30) commonest cause of dysphagia in India. Osteoarthropathy, Diffuse idiopathic skeletal hyperostosis (DISH) 2.5% (2) are significant cause of dysphagia though not common. No Patient was found to have globus hystericus.Conclusion: Osteodystrophy though not a common cause of dysphagia, but should be kept in mind when other apparent causes of it are negated and before diagnosing it as globus hystericus as in our study none of the patients were found to have globus. DOI:http://dx.doi.org/10.3329/bjo.v18i2.11992 Bangladesh J Otorhinolaryngol 2012; 18(2): 145-148